simplifying expressions – Fullsimplify not working perfectly

Here I am using the below code for a simplification.

DB = (Sigma)*(Sigma)*(Phi)*(Phi)
    BB = Sqrt(DB) // FullSimplify // PowerExpand
    g = 1/DB
    (Alpha)I = a(Phi)
    (Alpha) = (Alpha)I - 0.5*BB*D(BB, (Phi))
    (Alpha)s = (Alpha) - ((1/2)*BB*D(BB, (Phi)))
    UG = 0.375 (Sigma)^2
    Phi = UG - ((1/2)*(g*(Alpha)s*(Alpha)s)) // FullSimplify // 

But I am getting a result without cancelling the common term $$phi $$
Below is what I am getting. But I need to cancel the common terms. Here $$a, sigma $$are constants. $$phi$$ is a variable

Result I got: